The Association between Sport Participation and Dietary Behaviors among Fourth Graders in the School Physical Activity and Nutrition Survey, 2009–2010. Issue 2 (November 2014) - Dortch, Katherine Skala; Gay, Jennifer; Springer, Andrew; Kohl, Harold W.; Sharma, Shreela; Saxton, Debra; Wilson, Kim; Hoelscher, Deanna
Purpose: To determine the association between youth sport team participation and dietary behaviors among elementary school–aged children. Design: Cross-sectional survey. Setting: Public schools in Texas during 2009–2010. Subjects: A total of 5035 ethnically diverse fourth graders. Measures: Participation in organized sports teams, consumption of select food items (fruits, vegetables, beverages, sweets/snacks). Analysis: Multiple logistic regression was used to assess the association between each food item (eaten at least once on the previous day) and number of sports teams as the independent class variable (0, 1, 2, ≥3), adjusting for body mass index physical activity, socioeconomic status, and ethnicity. Results: Significant dose-response associations were observed between number of sports teams and consumption of fruits and vegetables. For boys, the likelihood of eating fruit and fruit-flavored drinks was significantly higher and the odds of drinking soda were lower with the number of teams. For girls, the likelihood of consuming green vegetables increased as sports teams participation increased, and participation was positively associated with diet soda consumption. A positive association was observed between the number of sports teams and scores on the Healthy Food Index for boys and girls. Conclusion: The findings that sports participation is associated with consumption of fruits and vegetables and lower consumption of soda suggest that efforts should be focused on supporting youth team sports to promote healthier food choices. Since sports are available to all ages, sports may be an important venue for promoting healthier dietary behaviors.